Announcement of conversion of Journal of Synchrotron Radiation to 100% open access from January 2022 - Office, Editorial (Journal of synchrotron radiation, 2020)
The proposed conversion of Journal of Synchrotron Radiation to 100% open access from January 2022 is announced. The proposed conversion of Journal of Synchrotron Radiation to 100% open access from January 2022 is announced.